Chemical constituents and biological activities of Callicarpa maingayi leaves - Ado, Muhammad Abubakar; Abas, Faridah; Leong, Sze Wei; Shaari, Khozirah; Ismail, Intan Safinar; Mohd Ghazali, Hasanah; Lajis, Md. Nordin (Elsevier, 2016)
Plants have an extensive diversity of natural phytochemicals that are used as a source of medicine. In this study the methanolic leaf extract of Callicarpa maingayi together with its increasing polarity soluble fractions hexane (Hex), dichloromethane (DCM), ethyl acetate (EtOAc), n-butanol (n-BuOH), and aqueous (Aq) fractions were examined on antioxidant, acetylcholinesterase (AChE), tyrosinase, and α-glucosidase inhibitory activities. Liquid chromatography-diode array detection-electrospray ionization-tandem mass spectrometry (LC-DAD-ESIMS/MS) was used to analyze the most bioactive fractions (EtOAc and n-BuOH). A total of 20 compounds were tentatively identified in these two active fractions. Forsythoside B, acteoside, isoacteoside, isocampneoside II, apigenin 7-O-rutinoside and kaempferol 3-sulfate-7-arabinopyranoside were identified by comparing with the reference standard. Other compounds including cistanoside F, apigenin 6-C-glucoside-8-C-glucoside, β-OH-forsythoside B, campneoside II, rhamnazin 3-O-rutinoside, campneoside I, eukovoside, acacetin diglucoronide, acacetin 7-O-glucuronide, β-OH-poliumoside, poliumoside as well as 3 isomers of 2′-acetylacteoside were tentatively identified based on their UV spectra and MS/MS data. All of the compounds were reported from this species for the first time. The results have indicated the chemical constituents of C. maingayi that contributed to the biological activity and thus, it may have potential application toward the development of nutraceutical and medicinal preparations.